Comparison and Optimization of Different Protein Nitrogen Quantitation and Residual Protein Characterization Methods in Dietary Fiber Preparations - Urbat, Felix; Müller, Patrick; Hildebrand, Andreas; Wefers, Daniel; Bunzel, Mirko (Frontiers in Nutrition, 2019)
Proteins are plant cell wall components but they are not included in the definition of dietary fiber. Therefore, dietary fiber preparations have to be corrected for their residual protein contents. This is commonly done by calculating the residual protein concentrations from the nitrogen contents after Kjeldahl digestion. Here, three different methods to determine nitrogen in Kjeldahl digests were compared: conventional titration with hydrochloric acid after steam distillation, a colorimetric assay (24-well microplates and cuvettes), and the determination by using an ammonia selective electrode. All assays gave similar results but detection using the ammonia ion selective electrode was found to be the most time-efficient approach. Also, an amino-acid profiling method, which is not based on commercial kits and which is suitable for routine analysis of dietary fiber preparations, was established. For this purpose, an HPLC-FLD method following amino acid derivatization using 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC) was optimized for fiber samples. Although all commonly used dietary fiber preparation methods involve the application of proteases the amino acid profiles of fiber samples from different sources were shown to be quite diverse. Considering the amino acid composition of the residual protein in various dietary fiber preparations, residual protein is probably not only based on structural proteins.